A Perceptual Learning Approach to the Whorfian Hypothesis: Supervised Classification of Motion. Issue 3 (19th June 2016) - Athanasopoulos, Panos; Albright, Daniel
Abstract: Recent research on the relationship between grammatical aspect and motion event cognition has shown that speakers of nonaspect languages (e.g., German, Swedish) attend to event endpoints more than speakers of aspect languages (e.g., English, Spanish). In this study, we took a perceptual learning approach to the Whorfian hypothesis, training native English speakers to categorize events either in an English‐like way (same‐language bias) or in a Swedish‐like way (other‐language bias), with and without verbal interference in English. Results showed that successful learning occurred in both language conditions. However, verbal interference disrupted learning only in the condition where the perceptual dimension to be learned was also salient in the participant's native language. This revealed selective language influence depending on the associative or dissociative relationship between the linguistic features occurring in the observer's native language and the perceptual features of the stimuli presented to them. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible in the IRIS digital repository athttp://www.iris‐database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .